Quality of Life of HIV/AIDS Patients: The Influence of CD4 Count on It - Chatterjee, Supantha; Akbar, Fasihul; Das, Nivedita; Ray, Kuntala; Bandyopadhyay, Sanjib; Singh, Manish Kumar (National Journal of Community Medicine, 2016)
Introduction: The HIV pandemic had a prevalence of 0.27% with 20.9 lakhs PLHIV in the year 2011.Decreased CD4 counts and associated opportunistic infections affects their Quality of Life. Objective: The objective of the study was to assess the association between CD4 counts and Quality of Life (QOL). Material and Methods: A cross-sectional study was conducted among 558 subjects visiting ART centre of Burdwan Medical College aged ≥ 15 years. Information regarding Socio-demographic variables was taken and Quality of Life (QOL) assessed by WHOQOL-BREF (Bengali version). Results and Analysis: Majority of the 558 subjects were Male (6.9%), Hindu (80.1%) and aged between 25-34 years (44.6%). 32.6% subjects had CD4 count < 200 mm3. Increased CD4 count was associated with higher QOL which was found to be statistically significant. Conclusion: QOL of HIV patient is influenced to a great extent by CD4 Count